Pengaruh Transfer Pricing Terhadap Kepatuhan Pajak Dengan Pertumbuhan Penjualan Sebagai Variabel Moderasi - Farahiyah, Alfira; Suhardianto, Novrys (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to provide empirical evidence of the influence of transfer pricing on tax compliance with sales growth as a moderating variable. The population used in this research is all non-financial companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The sample in this research was 1202 companies using purposive sampling with criteria written by the researcher. This research uses quantitative methods by conducting descriptive tests, correlation tests, and multiple linear regression tests using Stata 14. The results of this research indicate that transfer pricing has a negative influence on tax compliance. On the other hand, the research results show that sales growth cannot moderate the effect of transfer pricing on tax compliance. Thus, the results of this research do not support the legitimacy theory which states that companies always try to gain legitimacy or good recognition from stakeholders for the sustainability of the company's business. This research also uses control variables that represent company characteristics. The control variables of this research are profitability (ROA), company size (SIZE), and Leverage (LEV). Of these three variables, ROA in this study has a significant negative effect on tax compliance and company size in this study has a significant negative effect on tax compliance